Latin American Scholars Home In on Relations with China - Stallings, Barbara (2024)
As China has become a more important actor in Latin America and the Caribbean (LAC), scholars in this region have shown an increasing interest in studying the resulting challenges this poses. Most recent work has centered on economics (trade between China and LAC and finance from China), or on the consequences for environmental, social, and governance issues, although some scholars have focused on the impacts of US – China conflict in the region. In all cases, the question tends to be whether LAC countries are benefiting from the greater Chinese presence or whether problems outweigh the potential gains. We point out the leading research centers and scholars studying these questions and discuss the main debates around them. We conclude with a set of recommendations to improve the quality of research, including the need for better data and more collaboration with Chinese colleagues as well as the importance of transparency about the sources of finance and potential biases in work on this growing area of interest.